EVALUATION OF PROTECTIVE EFFECT OF AEGLE MARMELOS FRUITS EXTRACTS AGAINST STREPTOZOTOCIN-INDUCED TYPE 1 DIABETES MELLITUS IN RAT’S MODEL - AL-SHAMI, ALI SALMAN; JHA, DEEPAK KUMAR; BABUKUTTY, BLESSY ELIZABETH; HAQUE, MOHIBUL; KHADKA, JEEVAN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study aims to investigate the activity of methanolic extract of Aegle marmelos on Type I anti-diabetic in STZ induced in rat’s model. Methods: Extracted A. marmelos fruits were evaluated for anti-diabetic activity. Type I Diabetes has been induced in Wistar rats through STZ 65 mg/ kg/b.w.I.P. During the experiment, the rat’s body weight and fasting blood sugar levels were monitored. At the end of the study, animals in all groups have been sacrificed and biochemical parameters such as lipid profile, C-Peptide, HbA1c, serum insulin, pancreatic insulin, and histology of the pancreas have been observed. Furthermore, levels of antioxidant enzymes superoxide dismutase, catalase, and lipid peroxidation were measured. Results: The observed extract A. marmelos was proven to be safe in the toxicity findings. It has been shown an in vivo significant effect to manage diabetic markers such as weight gain, blood glucose, lipid profile, C-Peptide, HbA1c, the release of insulin secretion, and pancreatic insulin. The diabetic pancreas of rats has been observed to fall over beta cell density and disruption of normal architecture, but treated groups have been determined to restore the mass over beta cells. Elevated oxidative enzymes also have been viewed to control the treatment with A. marmelos. Conclusion: All its findings and phytoconstituents existing inside the extract must stay the viable chemical materials involved in the prevention of diabetes